Kebaikan atau Ancaman? Model Analytic Hierarchy Process untuk Penilaian Risiko Pendanaan Terorisme - I Made Wisnu Wardhana (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2025)
Non-profit organisations (NPOs) in Indonesia remain highly vulnerable to exploitation for terrorism financing despite the existence of legal and regulatory frameworks. Both registered and unregistered entities are often misused under humanitarian, religious, or educational fronts, exposing significant gaps in oversight. This study develops an Analytic Hierarchy Process (AHP)-based framework to systematically assess the terrorism financing risks of NPOs. Eight key indicators identified from prior qualitative research are categorised into two dimensions (internal and external) and weighted according to their relative significance. Eleven verified case studies of NPOs involved in terrorism financing were analysed using this model. The analysis produces quantifiable risk scores that are visualised in a two-dimensional matrix, classifying NPOs into low, moderate, or high-risk categories. Findings reveal that high-risk NPOs are typically unregistered, utilise personal bank accounts, and maintain direct or ideological links with domestic and transnational terrorist networks. The proposed AHP model provides an objective and operational tool for intelligence and regulatory authorities to prioritise supervision and allocate resources effectively, thereby strengthening Indonesia’s risk-based approach to counter-terrorism financing and offering potential adaptability within broader regional frameworks.